Probabilistic Optimization Of Incorporating Security Ciphers And Encryption Of Data Storage In Cloud - K.Haripriya, V.Lavanya, (International Journal of Advanced Science and Technology, 2020)
Cloud computing is the next stage of information technology.Itexportsrelateddatabasestothevarioushuge centres where the work is not trust worthy. Cloud data storagesecurityismainlyfocusedwhichplayavitalrole regarding quality services. To make sure that user’sdata is correct or wrong in cloud, Advanced Encryption Standard and other cryptographic algorithms are proposed. Analysis of security and performance calculations are done which explains that the proposed scheme is highly efficient. Parallel data processing in clouds is developed as it has come out now a days and research for parallel security has been a challenge from past few years is the data processing framework to explicitly utilize the dynamic storage along with data security. In the generation of IT organization service level agreement in the basis of security is not an important one. But now it has become a mandatory matter to secure the sensitive data and for corruption detection.